The key predictive indicators of efficiency among the applicants of accounting discipline: an empirical study of mathematics excellency - Zandi Pour Joopari, GholamReza; Shahabi , Alireza; Bagheri, Mojtaba (David Publishing Company., 2012)
Many organizations and universities wish to identify efficient and high caliber applicants who could excel over the Accounting discipline while scholarships and admissions are still not offered. It is believed that undergraduate accounting students with major in mathematics from pre-university institutes perform much better than those with arts or social sciences back grounds. This paper examines the mathematics perception level as well as pre-university’s CGPAs as main indicators of efficiency and better performance for accounting undergraduate students. By choosing all accounting undergraduates candidates whom had been admitted for 2009-2010 academic-calendars in four different universities, students’ mathematical talents highly and to a lower extent the CGPAs will influence positively the performance in accounting courses.